Micropropagation of Eucalyptus maidenii elite trees - Sotelo, M.; Monza, J. (Agrociencia Uruguay, 2007)
A method to propagate in vitro elite genotypes of Eucalyptus globulus Labill. ssp. maidenii (F. Muell.) Kirkp. was successfully established. The most favourable period for plant material collection was November to April. In that period the time needed for an epicormic bud to sprout was smaller, and the ratio of sprouted branches and the average number of epicormic buds sprouted were higher than in the other collection time (March to July). To establish axenic cultures the best response was obtained when micropropagation was started from shoot tips. The shoots developed on the Quoirin and Lepoivre (1977) basal medium had the best shape, size and colour. In relation to the growth regulators the best response for multiplication was obtained with 6-benzilaminopurine (BA) and Indolebutyric acid (IBA) and the best treatment was 0.2 mg.L-1/0.02 mg.L-1 respectively. Five of 58 clones evaluated were considered to have a good response to multiplication. The best elongation treatment was BA 0.1 mg.L-1/IBA 0.5 mg.L-1. This treatment produced 4 shoots elongated per explant, sizing more than 2 cm. The rooting response was variable depending on the clone and the treatment, and it did not surpass 25%. The rooted shoots were successfully transferred into potting soil (1peat:11/2 coconut fibre:1sand) in the greenhouse. After 30 months of outplanted, the survival percentage observed was around 80%, a percentage comparable to that obtained on plantations established from seeds, according to the company registers.